2001
DOI: 10.1021/jo001634r
|View full text |Cite
|
Sign up to set email alerts
|

Polarity of the Transition State Controls the Reactivity of Related Charged Phenyl Radicals Toward Atom and Group Donors

Abstract: Polar effects are demonstrated to be a key factor in controlling the reactivities of related charged phenyl radicals in different exothermic atom and group abstraction reactions in the gas phase. The effects of various meta substituents on the phenyl radicals' reactivity were probed via the measurement of bimolecular reaction rate constants by using Fourier transform ion cyclotron resonance mass spectrometry. This approach requires an additional, charged substituent to be present in the phenyl radical to allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 53 publications
5
35
0
Order By: Relevance
“…This was attributed to the great calculated EA v (6.53 eV at the B3LYP/6-31+G(d)+ZPVE level of theory) of this radical compared to those of the other phenyl radicals (5.11 – 5.82 eV at the B3LYP/6-31+G(d)+ZPVE level of theory). 58 These findings further emphasize the importance of the ionic surface in controlling the barrier height in radical abstraction reactions, in agreement with the work by Donahue et al 130 …”
Section: Properties and Reactivitysupporting
confidence: 86%
See 1 more Smart Citation
“…This was attributed to the great calculated EA v (6.53 eV at the B3LYP/6-31+G(d)+ZPVE level of theory) of this radical compared to those of the other phenyl radicals (5.11 – 5.82 eV at the B3LYP/6-31+G(d)+ZPVE level of theory). 58 These findings further emphasize the importance of the ionic surface in controlling the barrier height in radical abstraction reactions, in agreement with the work by Donahue et al 130 …”
Section: Properties and Reactivitysupporting
confidence: 86%
“…This model has been used in a number of experimental studies to explain relative rates of radical reactions, including several reviewed here. 50,52,56,58,62,67 …”
Section: Properties and Reactivitymentioning
confidence: 99%
“…Polar effects (i.e., polarization of the transition state) play a major role in controlling these reactions [5][6][7]. However, no such studies have been reported for the analogous biradicals.…”
mentioning
confidence: 99%
“…Previous studies have suggested that the polarity of the transition state of a charged phenyl radical depends on the electrophilicity of the radical [11]. As the electrophilicity increases, the transition states for its reactions become more polar, which leads to lower transition state energies [12].…”
Section: Introductionmentioning
confidence: 99%